Soil Macropores Affect the Plant Biomass of Alpine Grassland on the Northeastern Tibetan Plateau - Zheng, Ying; Chen, Ning; Zhang, Can-kun; Dong, Xiao-xue; Zhao, Chang-ming (Frontiers in Ecology and Evolution, 2021)
Macropores are an important part of soil structure. However, in alpine regions, the effects of soil macropores on soil properties and vegetation growth are not clear. We used the X-ray computed tomography (CT) method to obtain 3D images and visualize the distribution and morphology of soil macropores. By combining principal component analysis (PCA) and stepwise regression methods, we studied the relationships between soil macropores and both soil properties and vegetation growth in three types of grassland (alpine degraded steppe (ADS), alpine typical steppe (ATS), and alpine meadow steppe (AMS)) on the Tibetan Plateau. More tubular and continuous macropores occurred in the soil profiles of the AMS and ATS than in that of the ADS. In addition, the AMS soil had the highest macropore number (925 ± 189), while the ADS soil had the lowest macropore number (537 ± 137). PCA and correlation analysis suggested that macroporosity (MP) has significant positive correlations with the contents of soil organic matter, total nitrogen (TN), available phosphorus (AP) and total phosphorus (TP) (p < 0.05). The two parameters with the greatest influence on aboveground and belowground biomass were the shape factor (p < 0.05) and MP (p < 0.05), respectively. However, there was no significant correlation between plant diversity and soil macropores. We conclude that the irregularity of soil macropores restricts the growth space of roots and causes plants to sacrifice the accumulation of aboveground biomass for that of roots to find suitable sites for nutrient and water absorption.